How to Consolidate and Diversify Tourism Activity in North Iceland:Cases of Siglufjörður and Dalvík - Ástríður Viðarsdóttir 1985- (2018)
Tourism in rural areas in Iceland has not been researched to a great extent. Previous research on the subject has focused mainly on the tourists themselves, and how they experience the country and their overall satisfaction. This Master’s thesis aims to identify the key-factors in tourism marketing in rural areas in Iceland, with focus on two rural towns, Siglufjörður and Dalvík, and how these methods can be implemented to other rural areas of the country. The research question therefore is How do the remote towns Siglufjörður and Dalvík attract tourists? What are the challenges they face and what opportunities do they have? In the thesis data will be collected through interviews with people in the tourism industry that have, in one way or another, been involved in marketing of these rural areas. The results of this study will hopefully be helpful for other rural areas in the country that lack knowledge on tourism marketing. Keywords: Tourism marketing, Tourism industry, Iceland tourism marketing, Rural areas in Iceland.